Chewing gum supplemented with Brassica oleracea var. capitata f. rubra extract for pH detecting of artificial saliva - Fifit Indriyantari; Aprilia Nur Pratiwi; Rizky Septiano Andian; Ida Bagus Alit Rai Sugiharta; Archadian Nuryanti (Majalah Kedokteran Gigi Indonesia, 2020)
The prevalence of oral diseases in Indonesia is 25,9% in 2018, the highest percentage is recorded being caused to dental caries. Oral condition which may be acidic due to foods is potential to cause dental caries, as oral bacteria activities such as S. mutans may transform foods into becoming acids. In current condition, it is difficult for people to detect their own acid and base oral condition independently. This study aimed to create an innovation of a chewing gum supplemented with red cabbage (Brassica oleracea var. capitata f. rubra) extract which has functions as oral pH detector. The chewing gum was made by mixing the maceration extract of red cabbage and gumbase. This study was performed by using a qualitative test of pH 1-13 buffer solution colour change and pH 5-9 artificial saliva which was added by the extract, and then tested with manufactured chewing gum. Anthocyanin level was tested by using a 520 and 700 nm UV-Vis spectrophotometer. The study resulted in colour change in colour qualitative test. On pH 5-9 artificial saliva, colour change happened in order of orange, orange-brown, brown, brown-green, and green, after it was mixed with chewing gum. Colour compatibility test on chewing gum and artificial saliva showed a compatibility percentage of 80. Chewing gum supplemented with red cabbage can be used as pH detector of pH 5-9 artificial saliva.